Factores relacionados con la presencia de perros en las calles de la ciudad de Santiago, Chile - Ibarra, Luis; Espínola, Fabián; Echeverría, Mario (Avances en Ciencias Veterinarias, 2006)
In roles to know which are the factors related to the dogs in the streets and as a contribution to designing of sanitary measures for canine population surveillance and controlling, a research was carried out in 34 districts from the Metropolitan Region that conform Santiago city. The sampling unit was the street block and the specific information was obtained through direct observation of 864 city blocks from Santiago, by giving a minimum of 25 city blocks by district, randomly chosen. The street canine population characteristics, the urban structure and the habitat were registered to investigate the relationship among them.The results show that the amount and types of dogs observed in the streets of Santiago are related to the existence of "shelter like" places and water and food sources in the urban structure of Santiago. The presence of dogs is also related to the garbage location in the street design, because the amount of dogs is significantly smaller if there are storing facilities or baskets in height that prevent the animal access to the garbage.